Peran Komunikasi Dialogis dan Modal Sosial dalam Pengembangan Desa Wisata Rotan Trangsan - Hidayat, Rafli; Dian Purworini (Persatuan Wartawan Indonesia, 2025)
This research is based on the great potential of Trangsan Village in the development of a tourism village. Trangsan Rattan Tourism Village is known as the largest rattan artisan industry in Central Java Province and the second largest in Indonesia. Dialogical communication between the Trangsan Village Government and the community can build active community participation and strengthen their social capital in the development of tourism villages. Social capital owned by the community, such as trust, social networks, and prevailing values and norms, is believed to play an important role in the development of tourism in the village. This research aims to describe the role of dialogic communication and social capital in the development of Trangsan Rattan Tourism Village. This research uses a qualitative method with a case study approach. Data collection was conducted by observation and interviewing various related parties, including the local community, tourism village managers and the village government. The results showed that the Trangsan Village government has implemented dialogic communication and utilized social capital well in developing Trangsan Rattan Tourism Village. The most dominant important factor is the existence of mutuality, closeness and trust between the village government and the community and stakeholders, as well as a strong social network, contributing to the development of the tourist village.